2017
DOI: 10.1177/1934578x1701200838
|View full text |Cite
|
Sign up to set email alerts
|

GC/MS Fingerprinting of Solvent Extracts and Essential Oils Obtained from Liverwort Species

Abstract: Studies concerning chemical profiling of the volatiles present in the solvent extracts from liverworts help to determine inter-and intraspecific relationships in this plant group. Due to the fact that the liverworts are morphologically very small and it is difficult to collect their sufficient amounts, there are still a few data concerning the chemistry of essential oils. The available data indicate however, that the components present in the essential oils can be used in chemosystematic studies of these spore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Quite similar, Ludwiczuk et al [ 21 ], demonstrated the use of volatile compounds as chemical markers for the identification of Conocephalum conicum cryptic species. The importance of the composition of volatile compounds as chemical markers is confirmed by the results of numerous studies of different liverwort species [ 8 , 18 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…Quite similar, Ludwiczuk et al [ 21 ], demonstrated the use of volatile compounds as chemical markers for the identification of Conocephalum conicum cryptic species. The importance of the composition of volatile compounds as chemical markers is confirmed by the results of numerous studies of different liverwort species [ 8 , 18 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Resultsmentioning
confidence: 83%
“…Many of these compounds occur only in liverworts and exhibit interesting biological activities [ 9 , 10 , 11 , 12 , 13 , 14 ]. These compounds are also a valuable source of markers for resolving taxonomic problems and identifying individual species [ 15 , 16 , 17 , 18 , 19 , 20 ]. Revealing differences in the composition of chemical compounds between closely related species is important not only for the identification of species but also for the clarification of evolutionary relationships between them [ 19 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Liverworts are the only group of plants with characteristic cellular structures, oil bodies, that are organelles surrounded by a single membrane [6,7]. In these structures, chemical compounds are synthesised and stored [8,9]. Chemotaxonomic studies of liverworts have shown the presence of specific compounds at the family, genus, and even species level [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…However, in recent times, species identification has often been performed based on molecular tools, including the fast-growing DNA barcoding proposed by [28]. Another method to identify taxonomically difficult species of liverworts is an analysis of the chemical composition of the compounds contained in plants [8,12,13]. Chemical composition analysis is a method for classifying and identifying plants based on confirmed differences and similarities in their biochemical composition.…”
Section: Introductionmentioning
confidence: 99%